2022
DOI: 10.1161/jaha.122.025936
|View full text |Cite
|
Sign up to set email alerts
|

Shift Work and the Risk of Cardiometabolic Multimorbidity Among Patients With Hypertension: A Prospective Cohort Study of UK Biobank

Abstract: Background Although the association between shift work and individual cardiometabolic diseases has been well studied, its role in the progression to cardiometabolic multimorbidity (CMM) remains unclear. In this study, we investigate the association between shift work and the incidence of CMM in patients with hypertension. Methods and Results This study is a population‐based and prospective cohort study on 36 939 UK Biobank participants. We used competin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
27
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(30 citation statements)
references
References 34 publications
3
27
0
Order By: Relevance
“…Several epidemiological studies and meta-analysis have demonstrated that sleep duration of 6-8 h is associated with lower cardiovascular risk and mortality (Cappuccio et al, 2011; Yang et al, 2022). By contrast, we found that 5-6 h of sleep was related to better vascular characteristics, which seems to disagree with the aforementioned studies.…”
Section: Discussionmentioning
confidence: 99%
“…Several epidemiological studies and meta-analysis have demonstrated that sleep duration of 6-8 h is associated with lower cardiovascular risk and mortality (Cappuccio et al, 2011; Yang et al, 2022). By contrast, we found that 5-6 h of sleep was related to better vascular characteristics, which seems to disagree with the aforementioned studies.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the work schedule information was assessed only at the baseline. Participants’ work status might change over time during the follow-up while people tend to stop doing shift or night shift work at an older age, which might bias our results toward the null hypothesis, resulting in an underestimation of the effect size [ 53 ]. Future prospective studies measuring the longitudinal change of employment status would be needed to assess the association of lifetime exposure to shift work with the risk of dementia.…”
Section: Discussionmentioning
confidence: 99%
“…Studies in shift workers demonstrated an association between shift work and vascular events like myocardial infarction and ischaemic stroke, and higher blood pressure. [83][84][85][86][87][88] Endogenous circadian clocks have been shown in vascular endothelial cells, vascular smooth muscle cells, fibroblasts, cardiomyocytes, and cardiac progenitor-like cells in the cardiovascular system of mice and humans. 89 Disruption of the light-dark cycle (10 h/10 h) inhibited the compensatory hypertrophy and normal remodeling of the cardiovascular tissue in the pressure overload cardiac hypertrophy mouse model.…”
Section: Impact Of Circadian Disruption On Cardiovascular Diseasesmentioning
confidence: 99%
“…Studies in shift workers demonstrated an association between shift work and vascular events like myocardial infarction and ischaemic stroke, and higher blood pressure 83–88 . Endogenous circadian clocks have been shown in vascular endothelial cells, vascular smooth muscle cells, fibroblasts, cardiomyocytes, and cardiac progenitor‐like cells in the cardiovascular system of mice and humans 89 .…”
Section: Chronodisruption and Its Impact On Healthmentioning
confidence: 99%